Le Regard de Cartier-Bresson sur les Anglais - Nicole Cloarec (Revue LISA)
In 1937 Henri Cartier-Bresson was sent to London to cover George VI’s coronation. The ceremony occurred at a moment of intense national exaltation after a decade of economic hardship and the constitutional crisis caused by Edward VIII’s decision to marry Mrs Simpson. However the photographer is not so much interested in the official images of the historical event as he is in its effects on the people who attend. Cartier-Bresson adopts a double decentering which gives the picture a fictional independence and invests it with benign mockery. Henri Cartier-Bresson was later to capture other important historical events such as George VI’s funeral in 1952 and Winston Churchill’s funeral in 1965. Both events testify to a unified nation which is otherwise shown to be profoundly marked by rigid social conventions. In particular, the artist seems fascinated by the formal compositions that emerge from the “social dance” of the upper class, but he also dramatises the accidental meeting of different social classes as being worlds completely apart.